Pengaruh Motivasi Ekonomi, Motivasi Karir, Motivasi Gelar, dan Biaya Pendidikan terhadap minat mahasiswa akuntansi untuk megikuti Pendidikan Profei Akuntansi (PPAk) - Hutomo, Yoyok Priyo; Fira, Syafira Agnita Aulia; Hambani, Susy; Warizal, Warizal (AkMen JURNAL ILMIAH, 2024)
This research aims to determine the influence of economic motivation, career motivation, degree motivation and education costs on accounting students' interest in taking Accounting Professional Education (PPAk). This research method is a quantitative method. Data analysis uses multiple regression analysis, the calculation process uses the IMB SPSS 23 program. The hypothesis tests used are simultaneous tests (F test), partial tests (t test), and coefficient of determination tests (R2 test). The unit of analysis used in this research is active accounting students Class of 2020 and 2021 from 5 private universities in Bogor with a sample size of 100 respondents. The results of the study show that economic motivation, career motivation, degree motivation, education costs have a simultaneous effect on Accounting students' interest in taking PPAk. Meanwhile, partially economic motivation has a negative and insignificant effect on accounting students' interest in taking PPAk. Career motivation and degree motivation partially have a positive and significant effect on accounting students' interest in taking PPAk. And educational costs partially have no effect on accounting students' interest in taking PPAk.